SELECTED REFLECTIONS ON EXTERNAL SUPPORT AND ENDOGENIZATION – WITH SPECIAL CONSIDERATION FOR THE EUROPEAN UNION - Fiedor, Bogusław (Ekonomika, 2010)
The paper starts with a brief discussion of two aspects of convergence hypothesis. The first one (theoretical) refers to standard growth theory, the second is of normative character and pertains to axiological aspects of socio-economic policy, also including the EU cohesion policy. Not aiming to provide any comprehensive evaluation of that policy from the viewpoint of its actual effect on elimination of differences in social and economic development among the European regions, the paper provides selected reflections concentrated on:• an attempt of formulating a viable interpretation of cohesion policy (CP) as a form of ‘regulated capitalism’; the attempt in question refers to the normative approach towards public regulation in a market economy but defines the general rationality and fundamental objective of cohesion policy in terms of setting activities directed towards provision of the public goods that stimulate and facilitate exchange of goods and services among regions, thus contributing to the dynamization and endogenization of growth in poor or less developed regions;• the need of growth endogenization as the main objective (and main condition) of effective implementation of cohesion policy, provided that the definition of such endogenization is broader than that employed in the new growth theory. In particular, not rejecting the new growth theory definition of endogenous growth, the author pays special attention to the necessity of maximizing the regional value added through raising the level of processing broadly understood region-specific economic, social and others factors and resources;• correlations between the effects of distribution and growth within the scope of cohesion policy. It is analyzed from the perspective of three important questions: (1) Are the aims of social cohesion and growth competitive, or mutually complementary and reinforcing? (2) Why the hypothesis of regional convergence fails to explain the EU perspective, despite two decades of ongoing efforts of implementing active cohesion policy and regional policy? (3) Whether, and to what degree, the elimination of differences in the level of regional development is a legitimate strategy in the light of the controversy ‘equality vs. effectiveness’.